PENEGAKAN HUKUM TERHADAP PECANDU DAN PENYALAHGUNA NARKOTIKA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (Studi Putusan Pengadilan Negeri Kisaran Nomor 296/Pid.Sus/2021/PN.Kis) - Adhar, Syamsul; Marlina, Marlina; Affan, Ibnu (LPPM YPITI, 2021)
Law enforcement against narcotics crimes has been widely carried out by law enforcers, as well as many perpetrators who have been sentenced to court decisions and are serving sentences in correctional institutions. The formulation of the problem in this thesis is how to regulate the law for narcotics addicts and abusers, How is law enforcement against narcotics addicts and users according to Law Number 35 of 2009 concerning narcotics, What is the basis for judges' considerations in making decisions against narcotics users and abusers in Decision Number 296 /Pid.Sus/2021/PN.Kis. The type of this research is normative juridical, namely research based on law and empirical juridical by conducting research at the Asahan Police Station. Data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. Drawing conclusions in this paper is carried out using deductive-inductive logic of thinking that is done with the theory that is used as a starting point for conducting research. The results of the study indicate that the legal regulation of narcotics crimes based on Law Number 35 of 2009 concerning Narcotics prioritizes rehabilitation of narcotics addicts and users, but the criminal sanctions for narcotics dealers and precursors are very high. Law enforcement against addicts and narcotics users according to Law Number 35 of 2009 concerning Narcotics includes non-penal policy countermeasures, namely pre-emptive (counseling) and preventive (prevention) efforts. The judge's consideration in making a decision against the perpetrators of narcotics crimes in the decision of the Kisaran District Court Number 296/Pid.Sus/2021/PN.Kis is that the defendant must be held accountable for his actions in accordance with the decision handed down by the judge, namely imprisonment for 9 (nine) years and a fine 1,000,000,000.00 (one billion rupiah) provided that if the fine is not paid, it will be replaced with imprisonment for 4 (four months) is appropriate for coaching to be carried out.